Smaller capillaries improve the small‐angle X‐ray scattering signal and sample consumption for biomacromolecular solutions. (27th June 2018) - Schroer, Martin A.; Blanchet, Clement E.; Gruzinov, Andrey Yu.; Gräwert, Melissa A.; Brennich, Martha E.; Hajizadeh, Nelly R.; Jeffries, Cy M.; Svergun, Dmitri I.
Abstract : Sample exposure cells of small‐angle X‐ray scattering instruments often utilize cylindrical capillaries where the diameter, or path length, is typically selected to balance between scattering and absorption. Here it is demonstrated that, for radiation‐sensitive solution samples, using capillaries with a diameter smaller than the optimal path length in combination with continuous sample flow improves the quality of the scattering signal for a given quantity of material. Abstract : Radiation damage by intense X‐ray beams at modern synchrotron facilities is one of the major complications for biological small‐angle X‐ray scattering (SAXS) investigations of macromolecules in solution. To limit the damage, samples are typically measured under a laminar flow through a cell (typically a capillary) such that fresh solution is continuously exposed to the beam during measurement. The diameter of the capillary that optimizes the scattering‐to‐absorption ratio at a given X‐ray wavelength can be calculated a priori based on fundamental physical properties. However, these well established scattering and absorption principles do not take into account the radiation susceptibility of the sample or the often very limited amounts of precious biological material available for an experiment. Here it is shown that, for biological solution SAXS, capillaries with smaller diameters than those calculated from simple scattering/absorption criteria allow for a better utilization of the available volumes of radiation‐sensitive samples. This is demonstrated by comparing two capillary diameters d i ( d i = 1.7 mm, close to optimal for 10 keV; and d i = 0.9 mm, which is nominally sub‐optimal) applied to study different protein solutions at various flow rates. The use of the smaller capillaries ultimately allows one to collect higher‐quality SAXS data from the limited amounts of purified biological macromolecules.